Retrieval performance of Qur'anic texts (Pimpinan Ar-Rahman) in Jawi and Rumi Malay - Fauziah binti Abdul Wahid (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2014)
The enhancement in technology has sped the search process making more information available to users in a short amount of time. This also involves semantically enriched data for CLIR, which can either be in the form of different language or different writing system. This research investigated the retrieval performance of Quranic texts translation of Pimpinan Ar-Rahman in Jawi Malay (the old version of Malay Language) and Rumi Malay (the new Roman version of Malay Language) with different version of Malay Language and letter scripting considerations. Methodology implemented was by using queries formulated from FAQs written by Muslim scholars in authenticated printed sources produced in Malaysia. 50 FAQs were selected from Utusan Melayu newspaper for Jawi Malay queries and 50 FAQs from Berita Harian newspaper for Rumi Malay queries. Keyword(s) were derived by researcher from FAQs as queries to represent each FAQs. Queries were in Jawi Malay Original, Rumi Malay Transliterated, Rumi Malay Original and Jawi Malay Transliterated. Matching process was conducted by posting queries into Indri Retrieval. Result from matching process produced a results of list of Ayat and these Ayat undergo relevance judgement process that involved three human judges to determine the relevancy of FAQ topic and Ayat, while verifying the accuracy of retrieval. Data analysis that consisted of three measures; precision, recall and overlap, where data was obtained from Indri Retrieval test conducted in Indri search engine. Recall, precision and overlap discovered competency of Indri for handling multi-script Quranic texts produced high recall for both Jawi-96% and Rumi-91%, high precision for both Jawi-91% and Rumi-91%, followed by high overlap for Rumi-83% but moderate overlap for Jawi-72%. To conclude, this research is among research in retrieval of Quranic texts in multi-scripts Malay language retrieval that managed to outline state-of-the-art information retrieval system model for retrieval of multi-scripts for parallel corpus using Indri search engine in Roman and non-Roman scripts of Malay language.